2014
DOI: 10.1002/ejhf.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiac resynchronization therapy with implantable cardioverter defibrillator versus cardiac resynchronization therapy with pacemaker on mortality in heart failure patients: results of a high‐volume, single‐centre experience

Abstract: AimsThere are limited and contradictory data on the effects of CRT with implantable cardioverter defibrillator (CRT-D) on mortality as compared with CRT with pacemaker (CRT-P).Methods and resultsWe evaluated the long-term outcome of patients implanted with a CRT-D or CRT-P device in our high-volume single-centre experience. Data on all-cause mortality were derived from clinic visits and the Hungarian National Healthcare Fund Death Registry. Kaplan–Meier survival analyses and multivariate Cox regression models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 26 publications
4
46
0
Order By: Relevance
“…The number needed to treat (NNT) was 10. Ten studies showed significantly lower mortality rates with the CRT‐D device, while the remaining 9 were neutral . The observed I 2 values showed moderate heterogeneity within this analysis (I 2 =48%).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…The number needed to treat (NNT) was 10. Ten studies showed significantly lower mortality rates with the CRT‐D device, while the remaining 9 were neutral . The observed I 2 values showed moderate heterogeneity within this analysis (I 2 =48%).…”
Section: Resultsmentioning
confidence: 76%
“…Patients with indication for CRT typically also fulfill the Sudden Cardiac Death in Heart Failure Trial (SCD‐HeFT) inclusion criteria and are therefore candidates for an ICD. Although, we would expect CRT‐Ds to be advantageous because SCD is frequently a cause of death in patients with heart failure, data from randomized controlled trials, observational studies, and registries have not provided a clear support towards the advantage of CRT‐Ds over CRT‐Ps in that setting . Among other possible issues, lack of statistical power may be one of the possible causes of this uncertain benefit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aetiology of cardiomyopathy might be a relevant confounder and effect modifier in this analysis. Previous report suggested benefit of CRT-D over CRT-P in patients with ischaemic cardiomyopathy, but not in patients with non-ischaemic cardiomyopathy 6. It has been well described that female patients implanted with CRT devices more often present with non-ischaemic cardiomyopathy and derive greater improvement in echo outcomes and clinical outcomes than patients with ischaemic cardiomyopathy 7.…”
mentioning
confidence: 96%
“…In the accompanying editorial,2 Kutyifa notes that women accounted for only 15% of the CRT-D group but 42% of the CRT-P group, suggesting that sex may have affected the choice of CRT-P versus CRT-D and may have (perhaps inappropriately) influenced whether women received a CRT device at all. She also points out that under-representation of women, despite the attempt to correct for selection bias with propensity score analysis, limits the clinical applicability of this data until validated in other populations or, ideally, studied in a randomised controlled clinical trial.…”
mentioning
confidence: 99%